Simultaneous Measurement of ΔpH and Electron Transport in Chloroplast Thylakoids by 9-Aminoacridine Fluorescence - Evron, Yoav (American Society of Plant Physiologists, 2000)
Electron transport and the electrochemical proton gradient across the thylakoid membrane are two fundamental parameters of photosynthesis. A combination of the electron acceptor, ferricyanide and the ΔpH indicator, 9-aminoacridine, was used to measure simultaneously electron transport rates and ΔpH solely by changes in the fluorescence of 9-aminoacridine. This method yields values for the rate of electron transport that are comparable with those obtained by established methods. Using this method a relationship between the rate of electron transport and ΔpH at various uncoupler concentrations or light intensities was obtained. In addition, the method was used to study the effect of reducing the disulfide bridge in the γ-subunit of the chloroplast ATP synthase on the relation of electron transport to ΔpH. When the ATP synthase is reduced and alkylated, the threshold ΔpH at which the ATP synthase becomes leaky to protons is lower compared with the oxidized enzyme. Proton flow through the enzyme at a lower ΔpH may be a key step in initiation of ATP synthesis in the reduced enzyme and may be the way by which reduction of the disulfide bridge in the γ-subunit enables high rates of ATP synthesis at low ΔpH values.